Migration distance is positively associated with sex-linked genetic diversity in passerine birds. Issue 1 (2nd January 2016) - Gohli, J.; Lifjeld, J.T.; Albrecht, T.
Abstract : A recent comparative analysis of passerine birds found that the frequency of extra-pair paternity was positively associated with neutral genetic diversity. It has been hypothesised that migratory species have more extra-pair paternity than resident species, so we reanalysed the same comparative data set to test whether migration distance could also explain variation in genetic diversity. In this comparative analysis of 19 local populations from 18 passerine species, spanning year-round residents to long-distant migrants, we found that migration distance was positively correlated with sequence diversity at homologous nuclear Z-linked (sex) introns, but not with autosomal intronic diversity. This pattern contrasts with that of extra-pair paternity in the previous study, where extra-pair paternity was positively associated with autosomal diversity and not Z-linked diversity. We discuss several possible explanations for the correlation between Z-linked diversity and migration distance; effects that are specific to sex-linked genetic diversity may occur if migratory behaviour implies different selective regimes in the sexes or affects population structuring. These results suggest that significant amounts of genetic diversity at sex chromosomes and autosomes are shaped by different processes, and should therefore be analysed and interpreted independently in population genetics studies.